The implementability and proximal effects of a transdiagnostic mental health intervention for adolescents (Kort): protocol for a mixed-methods intensive longitudinal study - Thomas Engell; Siri Saugestad Helland; Emily Gabriela Vira; Silje Berg; Line Solheim Kvamme; John Kjøbli; Josefine Bergseth; Inga Brenne; Ragnhild Bang Nes; Espen Røysamb; Line Brager-Larsen; Anette Jeneson; et al. (BMC Health Services Research)
Abstract Background This protocol describes a study designed to test the implementability and proximal effects of a transdiagnostic mental health intervention for adolescents in school health services. The study is driven by the urgent need to address the rising mental health challenges among adolescents, exacerbated by the COVID-19 pandemic. Leveraging implementation science and evidence-informed intervention elements, this co-designed intervention focuses on emotion regulation (ER) as a central target for usable prevention and support. Methods The study employs a mixed-methods approach, integrating intensive longitudinal experience sampling (daily measures for 13 weeks), a micro trial, pre-, post-, and follow-up measures, audio recordings, and qualitative interviews to triangulate data from school nurses and adolescent participants. The research questions span the domains of intervention implementability, barriers and facilitators to implementation, proximal outcomes for adolescents’ emotion regulation, the mechanisms driving the intervention’s proximal effects, and response burden in experience sampling. The study aims to recruit a minimum of 25 health nurses and 46 adolescents. Discussion The study is novel in using mixed methods from multiple theoretical paradigms to examine ER as a dynamic process and transdiagnostic target outcome for promoting mental health and preventing disorders. Through daily diary and ecological momentary assessments, the study explores the intricacies of ER in real-life settings. Coupling the experience sampling with highly detailed fidelity measurement, we will observe adolescents’ day-to-day responses to intervention elements and how they affect emotion regulation. The integrated micro-trial also addresses concerns about response burden in experience sampling to optimize data collection strategies for future studies. The findings from this study can increase our understanding of ER as a mental health process, and contribute to the development of scalable, efficient, and context-appropriate mental health interventions in school nursing. Trial registration The ISRCTN-registry: ISRCTN14932526, registration date 04/04/2023.